Hybrid Coronary Revascularization: Early Outcomes and Midterm Follow-Up in Patients Undergoing Single or Multivessel Robotic TECAB and PCI. Issue 6 (November 2022) - Nisivaco, Sarah M.; Kitahara, Hiroto; Abutaleb, Abdul Rahman; Nathan, Sandeep; Balkhy, Husam H.
Objective: Hybrid coronary revascularization (HCR) is the integration of sternal-sparing coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in patients with multivessel coronary artery disease (CAD). It is traditionally performed with single-vessel bypass (left internal mammary artery [LIMA] to left anterior descending artery [LAD]) and PCI but can also be accomplished with multiple arterial grafts using bilateral IMA conduits. We sought to review our HCR experience over an 8-year period with robotic totally endoscopic coronary artery bypass (TECAB) and PCI. Methods: Of 694 patients undergoing beating-heart TECAB from August 2013 to June 2022, 306 patients were designated as intention-to-treat HCR candidates. Patients underwent PCI prior to, the same day as, or following TECAB, performed using single or bilateral IMA grafts. We retrospectively reviewed early and midterm outcomes up to 8 years in this cohort of patients. Results: The mean Society of Thoracic Surgeons predicted risk of mortality was 1.5% ± 2.5%. There were 44 patients (14%) who had ≥70% left main disease and 218 patients (71%) who had triple-vessel disease. A total of 193 patients (63%) underwent multivessel grafting (advanced HCR), with 83% bilateral IMA use. Mean operative time was 263 ± 80 min, and mean length of stay was 2.6 days. The mean number of vessels bypassed per patient was 1.7 ± 0.6. The mean number of vessels stented was 1.2 ± 0.5. Of the patients, 84% underwent TECAB first, 14% PCI first, and 2% same-day TECAB/PCI. Mortality was 0.6% (observed to expected ratio: 0.42). Early graft patency was 97% (328 of 339 grafts); LIMA-LAD patency was 98%. At 8-year follow-up (mean 37 ± 26 months), all-cause and cardiac-related mortality were 13% and 2.6%, respectively. Freedom from major adverse cardiac and cerebrovascular events was 92%. Conclusions: In patients with multivessel CAD, integrating robotic single and multivessel TECAB with PCI resulted in excellent early and midterm outcomes. In experienced hands, the robotic endoscopic approach allows the routine use of multiple arterial grafting during HCR.